혁신의료기기 규제 운영현황 비교를 통한 국내 통합심사제도의 실효성 분석 - 노소연; 최현경; 김유림; 장원석; So Yeon Noh; Hyeon Kyeong Choi; You Rim Kim; Won Seuk Jang (Journal of biomedical engineering research, 2025)
With rapid technological advancements, many countries have introduced regulatory programs to facilitate the market entry of innovative medical devices. This study investigates the designation systems for innovative medical devices in the United States, China, and South Korea, focusing on the period from 2020 to 2024, with particular attention to devices incorporating artificial intelligence (AI) technologies. The findings reveal that all three countries have implemented institutional frameworks to support the development and priority review of designated innovative medical devices. In particular, South Korea has actively promoted the early market entry of AI-based medical devices through the introduction of the Integrated Review Program in October 2022. Furthermore, analysis of designation trends in the digital healthcare sector shows that such devices account for 21% of the total designations in the United States, 9% in China, and 74% in South Korea, indicating South Korea's concentrated efforts in fostering AI-based medical device development. Based on these findings, this study examines the operational characteristics of South Korea's Integrated Review Program and proposes improvement strategies to enhance its effectiveness and promote greater utilization of regulatory benefits.